Survival and Differentiation of Adenovirus-Generated Induced Pluripotent Stem Cells Transplanted into the Rat Striatum. Issue 11 (November 2014) - Fink, Kyle D.; Rossignol, Julien; Lu, Ming; Lévêque, Xavier; Hulse, Travis D.; Crane, Andrew T.; Nerriere-Daguin, Veronique; Wyse, Robert D.; Starski, Phillip A.; Schloop, Matthew T.; Dues, Dylan J.; Witte, Steve J.; et al.
Induced pluripotent stem cells (iPSCs) offer certain advantages over embryonic stem cells in cell replacement therapy for a variety of neurological disorders. However, reliable procedures, whereby transplanted iPSCs can survive and differentiate into functional neurons, without forming tumors, have yet to be devised. Currently, retroviral or lentiviral reprogramming methods are often used to reprogram somatic cells. Although the use of these viruses has proven to be effective, formation of tumors often results following in vivo transplantation, possibly due to the integration of the reprogramming genes. The goal of the current study was to develop a new approach, using an adenovirus for reprogramming cells, characterize the iPSCs in vitro, and test their safety, survivability, and ability to differentiate into region-appropriate neurons following transplantation into the rat brain. To this end, iPSCs were derived from bone marrow-derived mesenchymal stem cells and tail-tip fibroblasts using a single cassette lentivirus or a combination of adenoviruses. The reprogramming efficiency and levels of pluripotency were compared using immunocytochemistry, flow cytometry, and real-time polymerase chain reaction. Our data indicate that adenovirus-generated iPSCs from tail-tip fibroblasts are as efficient as the method we used for lentiviral reprogramming. All generated iPSCs were also capable of differentiating into neuronal-like cells in vitro. To test the in vivo survivability and the ability to differentiate into region-specific neurons in the absence of tumor formation, 400, 000 of the iPSCs derived from tail-tip fibroblasts that were transfected with the adenovirus pair were transplanted into the striatum of adult, immune-competent rats. We observed that these iPSCs produced region-specific neuronal phenotypes, in the absence of tumor formation, at 90 days posttransplantation. These results suggest that adenovirus-generated iPSCs may provide a safe and viable means for neuronal replacement therapies.